133k views
5 votes
Use laws of exponents to simplify inside the parentheses of the given expression ((a ^ - 2 * b ^ 2)/(a ^ 2 * b ^ - 1)) ^ - 3

User Nandhos
by
5.3k points

2 Answers

5 votes

Answer:

its d

Explanation:

ur welcome

User Rbrundritt
by
5.2k points
5 votes

Answer:

Explanation:


[((a^(-2)*b^(2)))/((a^(2)*b^(-1)))]^(-3)=(a^(-2-2)*b^(2+1))^(-3)\\\\\\=(a^(-4)*b^(3))^(-3)=(a^(-4))^(-3)*(b^(3))^(-3)\\\\=a^(-4*-3)*b^(3*-3)=a^(12)*b^(-9)\\\\=(a^(12))/(b^(9))

Hint:
a^(-m)=(1)/(a^(m))\\\\a^(m)*a^(n)=a^(m+n)\\\\(a^(m))^(n)=a^(mn)\\

User Leesha
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.